Nitrous oxide consistently attenuates thermogenic and thermoperceptual responses to repetitive cold stress in humans - Moes, Maaike I.; Elia, Antonis; Gennser, Mikael; Eiken, Ola; Keramidas, Michail E. (Journal of applied physiology (1985), 2023)
Human thermoeffector plasticity was evaluated in response to prolonged iterative exposure to 30% N 2 O and moderate cold stress. Regardless of the duration of gas exposure, N 2 O-induced narcosis impaired in a persistent manner shivering thermogenesis and thermoperception. Divers are at enhanced risk of hypothermia, due to the independent action of the inspired inert gases on thermoregulation. Thus, narcosis induced by acute (≤2 h) exposure to either hyperbaric nitrogen or normobaric nitrous oxide (N 2 O) impairs shivering thermogenesis and accelerates body core cooling. Animal-based studies, however, have indicated that repeated and sustained N 2 O administration may prevent N 2 O-evoked hypometabolism. We, therefore, examined the effects of prolonged intermittent exposure to 30% N 2 O on human thermoeffector plasticity in response to moderate cold. Fourteen men participated in two ∼12-h sessions, during which they performed sequentially three 120-min cold-water immersions (CWIs) in 20°C water, separated by 120-min rewarming. During CWIs, subjects were breathing either normal air or a normoxic gas mixture containing 30% N 2 O. Rectal and skin temperatures, metabolic heat production (via indirect calorimetry), finger and forearm cutaneous vascular conductance (CVC; laser-Doppler fluxmetry/mean arterial pressure), and thermal sensation and comfort were monitored. N 2 O aggravated the drop in rectal temperature ( P = 0.01), especially during the first (by ∼0.3°C) and third (by ∼0.4°C) CWIs. N 2 O invariably blunted the cold-induced elevation of metabolic heat production by ∼22%–25% ( P < 0.001). During the initial ∼30 min of the first and second CWIs, N 2 O attenuated the cold-induced drop in finger ( P ≤ 0.001), but not in forearm CVC. N 2 O alleviated the sensation of coldness and thermal discomfort throughout ( P < 0.001). Thus, the present results demonstrate that, regardless of the cumulative duration of gas exposure, a subanesthetic dose of N 2 O depresses human thermoregulatory functions and precipitates the development of hypothermia. NEW & NOTEWORTHY Human thermoeffector plasticity was evaluated in response to prolonged iterative exposure to 30% N 2 O and moderate cold stress. Regardless of the duration of gas exposure, N 2 O-induced narcosis impaired in a persistent manner shivering thermogenesis and thermoperception.